Antibacterial Activities and Chemical Characterization of the Secondary Metabolites of Aspergillus terreus: Antibacterial Activities of the Secondary Metabolites of Aspergillus terreus - A. Naser, Lina; Jafer , Furdos N.; Aldhaher, Areej H. S. (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The present study aims to assess the biological impact of secondary metabolites isolated from Aspergillus terreus that have been isolated from the soil, the fungus was grown on a fermentation medium to produce secondary metabolism, and the fungal extract extracted from the secondary metabolite was purified and chemically characterized. Antimicrobial activities of bioactive compounds extracted from the secondary metabolite of Aspergillus terreus isolate were tested against five types of human pathogenic bacteria, Escherichia coli, Klebsiella spp., Staphylococcus aureus, Pseudomonas spp., and Proteus spp. The cytotoxicity was tested against a human blood solution. purification and chemical identification were carried out on a crude extract of A. terreus using TLC, GC–MS, and NMR data (1H proton and 13C carbon) analysis. The A. terreus secondary metabolite extract was effective against all isolated bacterial strains. The biocompatibility test showed no cytotoxic effect against a human blood solution used in different concentrations. One fraction was purified and identified as a novel compound: 2-(4-hydroxyphenyl) tetrahydro-3,4- furan diol. The results from a GC–MS analysis showed 18 peaks of the ethyl acetate extract of A. terreus metabolites, and the major compounds were bis(2-ethylhexyl) phthalate (47.60 %), n-hexadecanoic acid (16.41 %) and dodecamethylcyclohexasiloxane (9.79 %). According to the outcomes of this study, A. terreus can produce secondary metabolites that show potent activity against human pathogenic bacteria and are dependent sources for new secondary metabolites.